Synthesis of Platinum Complexes from N-Benzyl-2-Aminoethanethiol Derivatives - Mauro Vieira de Almeida; Laura Lúcia C. de Oliviera; Eloi Teixeira Cesar; Marcus Vinícius N. de Souza (The Scientific World Journal)
Twelve new platinum(II) complexes, analogs of cisplatin, containing a 2-aminoethanethiol N-substituted by several benzyl groups have been prepared and characterized in good yields. The ligands were obtained by reaction between 2-aminoethanethiol hydrochloride and different benzyl halides